Permaculture as Alternative Agriculture - Peeters, Bert (Kasarinlan: Philippine Journal of Third World Studies, 2012)
Lack of food sovereignty has been one of the Philippines’ perennial problems. Due to inadequacy of food supply, the needs or demands of the people could not be met, and the problem leads to the poverty of the nation and the malnutrition of its people. Many researches have been done by the Philippine government to identify solutions to this problem. In this study, the concept of permaculture is discussed as a means to solving the problem of food sovereignty in the Philippines. The study describes an existing pemaculture-development site in Cabiao, Nueva Ecija, called the Cabiokid Foundation. This site applies permaculture principles in all areas and nurtures natural ways to solve a wide range of problems, including lack of food sovereignty, to prevent malnutrition and poverty.
Keywords: permaculture; rural development; sustainable agriculture; Nueva Ecija